Study on the Water Ecology Protection and Water Environment Remediation Technology, focusing on the heavy metal removal - Zhao Zihan (E3S Web of Conferences)
Water environmental pollution has become a growing problem with the increase in pollutants released because of the expansion of human activities. Since water is peculiarly susceptible to pollution, water pollution control has garnered copious attention among the most crucial environmental conundrums. Therefore, water environment remediation is not only of great significance for river ecology, but also of theoretical and practical importance for sustainable human development. China’s central government passed the Yangtze River Protection Law in response to the need for changes in governance arrangements and cooperation. The purpose of this study is to explore the technology of heavy metal treatment in water environment remediation, to study and solve a series of problems such as water ecological maintenance methods, river desilting, and water body renewal. This paper will analyze the benefits of water environment remediation technologies and explore their potential for sustainable development, focusing on the removal of heavy metals from water body.